Business management competences and their relationship with the factors that limit the business growth of agroexporting MYPES of olive and derivatives of Tacna. 2018. - Sihuayro Larico, Dennys (2020)
Determine the relationship that exists between the managerial competencies of the entrepreneurs and the factors that limit the business growth of the agro-export MYPES of olive and Tacna derivatives. The research is cross-sectional correlation. According to the researcher's interference in the study, it is a non-experimental investigation. The population is limited to the MYPE entrepreneurs dedicated to the agro-exporter sector of olives and derivatives of the city of Tacna, the sample size selected applying the non-probabilistic sampling. The data processing involved Frequency tables, bar graphs, chi square association tests and Spearman's Rho correlation coefficient both evaluated at the 5% significance level. It was concluded that there is a significant relationship (p <0.05) between managerial competencies and the factors that limit the business growth of the agro-export MYPES of olive and Tacna derivatives in 2018. Although they present an average positive association (rho = 0.543), where a majority of 58.33% consider that the different managerial competencies for business management apply "almost always" while 41.67% indicate that they "always" consider management competence for driving and business decisions